Stock and Compensation. - Scholes, Myron S (Journal of Finance, 1991)
Compensation planning within firms creates important corporate financial problems. Theoretical models and empirical tests of hypotheses in this area should play a much larger role than currently in the modern theory of corporate finance. Employees fund a large proportion of their firm's activities through deferred compensation arrangements tied to the performance of their company. These arrangements are generally put in place for incentive reasons, to align the interests of employees more closely with those of shareholders. Moreover, tax rules encourage or discourage these arrangements at various times. Currently, both tax rules and incentive considerations encourage stock buyback programs to fund deferred compensation arrangements. Prior to the 1980s, however, tax rules favored funding in other than company stock, implying that employees likely held company stock for incentive and not for tax reasons during this time period.